Study on bond behaviour of stainless steel reinforced concrete. (October 2022) - Xu, Chunyi; Wang, Kaile; Gu, Ximin
Highlights: Both CSR concrete specimens and ASSR concrete specimens are mainly damaged by steel rebar pulling out. The failure mode of DSSR concrete specimens is mainly concrete splitting failure. The change of concrete strength has the greatest influence on bond slip of DSSR concrete, followed by CSR concrete, and finally ASSR concrete. By comparing τ - s curves of three kinds of reinforced concrete, CSR concrete has the best bond slip performance, followed by DSSR concrete, and finally ASSR concrete. The calculation formula of ultimate bond strength of SSR concrete is obtained, ASSR concrete: τ u = ( - 0.2 d l a + 1.48 c d + 18.08 ρ sv ) f t ; DSSR concrete: τ u = ( - 0.14 d l a + 1.32 c d + 138.31 ρ sv ) f t . The recommended value of SSR anchorage length is proposed, and the calculation formula of SSR concrete anchorage length is put forward, ASSR concrete: l ab = 0.203 f y f t d ; DSSR concrete: l ab = 0.159 f y f t d . Abstract: The stainless steel rebar (SSR) and concrete are mainly bonded to transfer force and coordinate deformation. Therefore, it is necessary to study the bond behavior of stainless steel reinforced concrete. In this paper, the reinforced concrete specimens of carbon steel rebar (CSR), austenitic stainless steel rebar(ASSR) and duplex stainless steel rebar (DSSR) are made by taking concrete strength, steel rebar diameter, anchorage length, thickness of concrete cover and stirrup ratio as test parameters. Through the pull-out test, the failure phenomenon, bond stress-slip curve, ultimate load and ultimate bond strength of three kinds of reinforced concrete specimens are compared. The influence regularity of different factors on the bond behavior of SSR concrete is studied.. The bond strength formulas of ASSR and DSSR concrete are obtained by data fitting. The test results show that: (1) Both CSR concrete specimens and ASSR concrete specimens are mainly damaged by steel pulling out; (2) The failure mode of DSSR concrete specimens is mainly concrete splitting failure; (3) The change of concrete strength has the greatest influence on bond slip of DSSR concrete, followed by CSR concrete, and finally ASSR concrete; (4) CSR concrete has the best bond slip performance, followed by DSSR concrete, and finally ASSR concrete; (5) The recommended design value and calculation formula of anchorage length of ASSR and DSSR are given.